An Investigation of Change in Mathematics, Science, and Literacy Education Pre-service Teachers’ TPACK - Tokmak, Hatice Sancar; Incikabi, Lutfi; Ozgelen, Sinan (Springer Science and Business Media LLC, 2012)
This quasi-experimental research study aimed to investigate the effect of technological, pedagogical, and content knowledge (TPACK)-based course design on mathematics, science, and literacy education pre-service teachers’ TPACK. Participants in the study consisted of 31 mathematics, 32 science, and 38 literacy education pre-service teachers who attended introduction to computers. To collect data, the technological pedagogical content knowledge self-efficacy instrument (TPACKSEI) developed by Graham et al. (2009) was applied before and after the course. The results showed significant improvements in all groups of pre-service teachers’ mathematics, science, and literacy education self efficacy on their TPACK. Moreover, there were no significant differences between natural science (mathematics and science education) and social science (literacy) for pre-service teachers’ TPACK. However, there were significant differences between natural science and social science pre-service teachers’ technological knowledge and technological content knowledge.
Keywords: 4. Education